AI in teacher education: Unlocking new dimensions in teaching support, inclusive learning, and digital literacy - Zhang, Jia; Zhang, Zhuo (Journal of computer assisted learning, 2024)
Background AI can positively influence teaching by offering support for classroom management, creating inclusive learning environments, enhancing digital skills, personalizing teaching methods, and strengthening teacher‐student relationships. Objectives This quantitative research study investigates the opportunities, difficulties, and consequences of incorporating AI into teacher education. Methods Data were collected through structured questionnaires from 202 college students and 68 staff members. The analysis was conducted using SPSS software. Results The study provides a novel contribution by its thorough investigation of the diverse effects of AI on teacher education. It offers beneficial perspectives on the possible benefits and challenges, illuminating the far‐reaching changes that AI could bring to the terrain of learning and instruction and teaching methods in the time yet to come. The research sought to assess the effect of AI adoption in teacher education across five main dimensions: (i) its influence on teaching support and classroom management, (ii) its role in creating inclusive and accessible learning environments, (iii) its contribution to improving teachers' digital literacy and computer skills, and enhancing access to digital teaching resources, (iv) its positive influence on identifying students' learning styles and facilitating the adoption of diverse teaching methods, and (v) its role in strengthening teacher‐student relationships through improved interactions. Conclusion The findings elucidate the promising opportunities that AI presents in the field of teacher education, along with the obstacles that require resolution for the effective fusion of AI educational settings. Lay Description What is currently known about this topic? AI has the potential to enhance various aspects of teaching, including classroom management and personalizing teaching methods. Incorporating AI into education has garnered significant interest due to its perceived benefits in improving learning outcomes. What does this paper add? This paper provides a comprehensive investigation into the effects of AI adoption in teacher education, highlighting both the opportunities and challenges associated with its implementation. It offers insights into how AI can influence different dimensions of teaching, such as classroom management, learning environment inclusivity, and teacher‐student relationships. Implications for practice/or policy The findings of this study underscore the importance of integrating AI into teacher education programs to leverage its potential benefits in enhancing teaching practices. Policymakers and educators should consider the implications of AI adoption in education and develop strategies to address challenges while maximizing the advantages of AI technologies in teaching and learning.